2018
DOI: 10.1080/14756366.2018.1545768
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of blood carbonic anhydrase activity of athletes performing interval and continuous running exercise at high altitude

Abstract: The effects of high-intensity interval and continuous exercise on erythrocytes carbonic anhydrase (CA, EC 4.2.1.1) activity levels were scarcely investigated up until now. Here we present a study focused on the CA activity from erythrocytes of athletes experiencing interval and continuous training for 6 weeks, during cold weather and at high altitude (> 1600 m). We observed a 50% increase in the blood CA activity at the second week after initiation of the training in both interval and continuos running groups,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
0
7
0
1
Order By: Relevance
“…Intensive muscular exercise induces the formation of lactate and CO 2 , which leads to intracellular acidosis. A previous study reported increased blood CA activity 2 weeks after starting interval training ( Tas et al, 2019 ). Therefore, the prompt elevation of CA-1 in EVs may be an adaptive reaction to correct for an acid–base imbalance brought on by HIIT-Ex.…”
Section: Discussionmentioning
confidence: 94%
“…Intensive muscular exercise induces the formation of lactate and CO 2 , which leads to intracellular acidosis. A previous study reported increased blood CA activity 2 weeks after starting interval training ( Tas et al, 2019 ). Therefore, the prompt elevation of CA-1 in EVs may be an adaptive reaction to correct for an acid–base imbalance brought on by HIIT-Ex.…”
Section: Discussionmentioning
confidence: 94%
“…Enzyme activity was determined spectrophotometrically by following the change in absorbance at 348 nm of 4‐nitrophenylacetate to 4‐nitrophenol over a period of 3 min at 25°C . The enzymatic reaction contained 1.4 mL 0.05 M Tris‐SO 4 buffer (pH 7.4), 1 mL 3 mM 4‐nitrophenylacetate, 0.5 mL H 2 O, and 0.1 mL enzyme solution, in a total volume of 3.0 mL . Inhibitory effects of compounds 3 – 14 were compared with AZA.…”
Section: Methodsmentioning
confidence: 99%
“…An Activity % − [Inhibitor] graph was drawn for each inhibitor . The curve‐fitting algorithm allowed for obtaining the IC 50 values, working at the lowest concentration of substrate of 0.15 mM, from which K I values were calculated . The catalytic activity of these enzymes was calculated from Lineweaver–Burk plots, as reported previously , and represent the mean from at least three different determinations.…”
Section: Methodsmentioning
confidence: 99%
“…[42] The CA I and II enzymatic reaction contained 1.4 mL 0.05 M Tris-SO 4 buffer (pH 7.4), 1 mL 3 mM 4-nitrophenylacetate, 0.5 mL H 2 O and 0.1 mL enzyme solution, in a total volume of 3.0 mL. [43][44][45][46] Inhibitory effects of compounds were compared with AZA. Different inhibitor concentrations were used and all compounds were tested in triplicate at each concentration used.…”
Section: Hca I and Ii Inhibition Assaymentioning
confidence: 99%